Investigation of the sorption characteristics of water lettuce (WL) as a potential low-cost biosorbent for the removal of methyl violet 2B. Issue 18 (14th April 2016) - Lim, Linda B.L.; Priyantha, Namal; Chan, Chin Mei; Matassan, Diyanah; Chieng, Hei Ing; Kooh, Muhammad Raziq Rahimi
Abstract: Pistia stratiotes L . (water lettuce or WL) was investigated for its potential as an effective low-cost biosorbent for the removal of methyl violet 2B (MV). Equilibrium isotherm for the adsorption of MV, fitted using six different isotherm models followed by error analyses, indicates that the maximum biosorption capacity ( q max ) is 0.68 mmol g −1 (267.6 mg g −1 ) and that both the Langmuir and Sips isotherm models lead to good correlation with experimental data. Investigation on effects of pH, ionic strengths, and pre-treatment of the biosorbent on the extent of biosorption indicates the effect of these parameters on MV–biosorbent interaction. Kinetics of the interaction of MV and the biosorbent is fast with more than 50% dye being removed and follows the pseudo-second-order model.